APLIKASI DASHBOARD UNTUK ANALISA PEMETAAN HOTSPOT PADA SAMPAH LAUT DI INDONESIA - Amalia Nurain; Alexander Assisi; Kenny Yan; Dedi Trisnawarman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Garbage is very much around the human environment, not only on land, but also in the sea. It is necessary to carry out special monitoring of marine debris. The purpose of this research is to build a dashboard application to map hotspots in marine waste processing. Dashboards can be a solution in monitoring marine debris. The tools used are Microsoft PowerBI by displaying visualizations of marine debris data and demographic data. The dashboard development method uses the basic principles of Few references to display key performance indicators (KPIs), namely: the amount of waste that has been generated, transported, and not handled. The KPI value is then connected with latitude and longitude data to determine the coordinates of the location on the map, then the data is analyzed using a TreeMap graph and a line graph associated with the existing data attributes. The results obtained describe the distribution of Indonesia's marine litter hotspots, how much waste is produced, transported waste, untreated waste, and its distribution in several cities.